Generation and Evaluation of Modified Opaque-2 Popcorn Suggests a Route to Quality Protein Popcorn - Ren, Ying; Yobi, Abou; Marshall, Leandra; Angelovici, Ruthie; Rodriguez, Oscar; Holding, David R. (Frontiers in Plant Science, 2018)
Introducing traits from dent corn to popcorn is challenging because it is difficult to recover adequate popping characteristics. QPM (Quality Protein Maize) is a dent corn variety carrying the opaque-2 (o2) mutation, specifying increased amounts of normally limiting essential amino acids, and modifier genes which restore the wild type vitreous kernel phenotype. In this study, we introgressed o2 and selected for endosperm modification using vitreousness and high 27-kD gamma zein content. In this way, we recovered high-lysine, fully poppable Quality Protein Popcorn (QPP). BC2F4 individuals with vitreous kernels were confirmed to be o2 mutants by both genotyping and SDS-PAGE. Amino acid profiling of BC2F4 individuals showed that they all have significantly increased lysine compared with popcorn parental lines. Principal Component Analysis of the amino acid profiles showed that all introgressions were grouped with corresponding QPM parental lines. Popping analysis of the BC2F5 individuals showed that while there is variability in popping volume between lines, some lines show equivalent popping to the popcorn parent. In this proof-of-concept study for QPP, we have shown that it is possible to rapidly recover sufficient popcorn characteristics in a modified o2 background using simple phenotypic, biochemical and genetic selection. Furthermore, this shows increased γ-zein is an acceptable substitute for α-zein for full poppability. Since we have developed multiple QPP introgressions, this gives good scope for ongoing hybrid production and future evaluation of agronomic performance and selection of elite hybrids. In a wider context, this study shows the potential for breeding beneficial traits into popcorn for agronomic improvement.